Analysis Of Patient Satisfaction Toward Clinic Services Using Integration Of Service Quality And Kano Model (a Study Of Patients At Klinik Harapan Sehat In Cianjur) - Dwita Nurhaliza Kharisma; Husni Amani; Ima Normalia Kusmayanti (eProceedings of Engineering, 2019)
Abstrak Harapan Sehat is a clinic engaged in healthcare sector. Klinik Harapan Sehat has a good performance. However, there are not many people that have discovered the advantages provided by the clinic. Despite having the good performance and implementing several targeted programs, Klinik Harapan Sehat is still experiencing fluctuation that has not been significant. In this research, the analysis of patient satisfaction towards service quality was performed using Kano model and integration method of service quality at Klinik Harapan Sehat. In addition, the attributes were also identified on several respondents to be analyzed and applied in accordance with the capacity of Klinik Harapan Sehat to find out the level of patient satisfaction and quality towards the service in order to improve service standardization of the clinic. The purpose of this research is to identify the true customer needs that are necessarily implemented by Klinik Harapan Sehat based on the level of patient satisfaction towards the service at Klinik Harapan Sehat and the service quality which include tangibles, reliability, responsiveness, assurance, and empathy dimensions and to find out the relation between patient satisfaction and service fulfillment at Klinik Harapan Sehat through Kano model. There were 5 attributes from the respondents that were needed to be maintained and 10 attributes that were needed to be prioritized. The prioritized attributes were identified and the recommendations were provided. Keywords: Need Attributes, Service Quality, Kano Model, True Customer Needs.